PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, BRAND IMAGE TERHADAP KEPUASAN PELANGGAN - Muhammad Daffa Mediansyah; Chatarina Yunita Tarigan (LPPM Universitas Asa Indonesia, 2025)
This study aims to determine the influence of product quality, price perception, and brand image on customer satisfaction of Martabak Pecenongan 78 Pinang Ranti branch, East Jakarta. This study uses a quantitative approach with a survey method, where respondents are selected using purposive sampling techniques , namely consumers who have made purchases more than twice. The number of respondents was 100 people. Data were analyzed using multiple linear regression with the help of SPSS 26 software. The results of the study show that product quality and price perception have a positive and significant effect on customer satisfaction. Meanwhile, brand image does not have a significant effect and instead shows the direction of negative influence. Simultaneously, these three variables were able to explain 86.7% of the variation in customer satisfaction. These findings confirm the importance of maintaining product quality and setting competitive prices. Although the brand image has not shown a significant influence, it is still necessary to strengthen the brand image to support positive perception and customer loyalty in the future. This research provides strategic insights for the development of culinary businesses based on customer satisfaction